Effectiveness Of TPACK-Based PjBL Model in Indonesian Language Subjects in Increasing Learning Motivation Of Elementary School Students - M Choirul Muzaini; Prastowo, Andi; Elvandari Maulana (Genderang Asa: Journal of Primary Education, 2024)
The purpose of this study was to identify the effectiveness of the TPACK-based PjBL model in Indonesian language subjects in increasing the learning motivation of elementary school students. This research is a classroom action research conducted in two cycles using the spiral model by C. Kemmis and MC. Taggart. The research subjects consisted of 33 fourth grade students of SD N Lempayangan 1. Data collection techniques used observation, questionnaire, test, and interview methods. The results showed that the application of the TPACK-based PjBL model showed a significant increase in teacher activity from cycle I (67.32%) to cycle II (88.45%), with a good category. Student activities also increased from cycle I (75.38%) to cycle II (89.32%), with a good category. Results from the questionnaire showed that students' learning motivation increased from 65% to 90%. Test results showed an improvement in student learning outcomes, with an average pretest score of 68 and posttest score of 85, an increase of 17 points. Students' response to learning was also very positive, increasing from 63% who felt less interested before to 93% who felt more interested and motivated after applying this model, compared to conventional learning methods.